2015
DOI: 10.18632/oncotarget.5324
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as prognostic molecular signatures in renal cell carcinoma: a systematic review and meta-analysis

Abstract: This is a systematic review of studies investigating the prognostic value of different microRNAs (miRs) in renal cell carcinoma (RCC). Twenty-seven relevant studies were identified, with a total of 2578 subjects. We found that elevated expression of miR-21, miR-1260b, miR-210, miR-100, miR-125b, miR-221, miR-630, and miR-497 was associated with a poor prognosis in RCC patients. Conversely, decreased expression of miR-106b, miR-99a, miR-1826, miR-215, miR-217, miR-187, miR-129–3p, miR-23b, miR-27b, and miR-126 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
2
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 77 publications
(110 reference statements)
2
89
2
1
Order By: Relevance
“…As RCC is the most common type of kidney cancer, with an increasing incidence (7,24), it is important to explore and understand the tumor biology of this malignancy in order to find new early diagnostic markers and therapeutic approaches. Cancer cells aquire various mechanisms by which they escape apoptosis, become immortal, or provide to them at least a survival advantage compared to non-malignant cells (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As RCC is the most common type of kidney cancer, with an increasing incidence (7,24), it is important to explore and understand the tumor biology of this malignancy in order to find new early diagnostic markers and therapeutic approaches. Cancer cells aquire various mechanisms by which they escape apoptosis, become immortal, or provide to them at least a survival advantage compared to non-malignant cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is more necessary than ever to understand its tumor biology and explore new targets for further therapeutic approaches and prognostic options (6). Former studies suggested that among others, a misguided microRNA expression pattern may be involved in tumor initiation and progression in RCC (7,8). Among such mechanisms, small regulatory RNAs, so-called microRNAs (miRs), can operate as controllers of different proccesses in tumorigenesis, such as cell migration and differentiation, as well as metastasis and apoptosis (9-11).…”
mentioning
confidence: 99%
“…RCC patients with positive microRNA-21 exhibit shorter disease-free and overall survival rates (13). Therefore, microRNA-21 is proposed as a diagnostic and prognostic marker in renal cell carcinoma (15,44,45). So, in this study influence of cordythat cordycepin dose-dependently down-regulated microRNA-21 levels in Caki-1 cells (Fig.…”
Section: Effects Of Cordycepin On Renal Cell Carcinoma Caki-1 Cellsmentioning
confidence: 62%
“…Therefore, in this present study, we aimed to identify new miRNA biomarker that could be used as predictor for the overall survival of GC patients and also with the hope to reveal the underlying mechanism of how miRNA participated in the development of GC. miR-100 has been found aberrant expressed in several human cancers but its role in tumorigenesis is still controversial (16)(17)(18)(19)(20). The reason for that might be it can regulate different downstream target genes and therefore it can have different and even opposite functions in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-100 was found to acting as tumor suppressor by deregulation its target genes in hepatocellular carcinoma (17), epithelial ovarian cancer (18), and breast cancer (19). However, miR-100 was also found to acting as oncogene in renal cell carcinoma (20) and acute myeloid leukemia (16). Therefore, the clinical significance of miR-100 in GC and the underlying mechanism still remained to be elucidated.…”
Section: Introductionmentioning
confidence: 99%